Induced pluripotent stem cells derived from mouse germ cells - Khan, Nora (AUC Knowledge Fountain, 2017)
While embryonic stem cells are well known to give rise to tissues comprising all three germ layers, only recently was it found that embryonic-like stem cells could be derived from the postnatal mice testis in culture. Embryonic-like stem cells from postnatal testes have shown that they can undertake most if not all, the functions of embryonic stem cells. Most recent reports have demonstrated that somatic cells can be induced to pluripotent stem cells, mostly with the addition of genes. However, the aim of this work is to explore the potential of testicular cells to become pluripotent, including expression of pluripotency-associated genes, and embryonic stem cells morphology, without the addition of genes. To accomplish our aim, we have sacrificed 15 CD-1 Swiss albino mice (8-10 weeks) and harvested cells from the testes using both mechanical and enzymatic digestion technique to generate single cell suspension. Isolated cells from the testes at day 1 along with embryonic-like stem cells at day 14 have been characterized via Reverse Transcription - Polymerase Chain Reaction (RT-PCR) using germ cells marker VASA, embryonic stem cells markers Nanog, cripto TDGF1, Esg1, and Thy1. Furthermore, Immunophenotyping was performed via Flow Cytometer using embryonic-like stem cells marker SOX2, CD 90 (Thy1), CD15 (SSEA-1), CD117 (c-kit), and CD133. Our results showed success in culturing cells harvested from the testes, these cells were reprogrammed and had the characteristics of embryonic stem cell. RT-PCR results confirmed the expression of VASA gene at day 1; these cells did not express embryonic stem cells markers (Nanog, cripto TDGF1, Esg1, and Thy1). However, embryonic-like stem cells at day 14 showed the expression of the previously mentioned embryonic stem cells markers, and did not express Vasa, which is a germ cell marker. Immunophenotyping results showed a noticed elevation in embryonic stem cells markers (SOX2, CD 90, CD15, CD117, and CD133) at day 14 compared to those at day 1. Here we report that embryonic-like stem cells can be derived from postnatal mice testis. However, further studies are required to assure the optimum value of embryonic-like stem cells that is dedifferentiated from mice testis before being used clinically in human.